Progress in Simulations of Unsteady Projectile Aerodynamics - Sahu, J.; Heavey, K. R. (2010 DoD High Performance Computing Modernization Program Users Group Conference, 2010)
As part of the multi-year Challenge Project, research efforts have been ongoing for developing and applying advanced time-accurate computational fluid dynamics (CFD) methods for computation of unsteady projectile aerodynamics both with and without control maneuvers. One method is a time-accurate sweep procedure being developed for rapid generation of a database of static aerodynamic coefficients. The other time-accurate method involves coupling of CFD and rigid body dynamics (RBD) for simulations of physics-based "Virtual Fly-Outs" of munitions on high performance computing platforms similar to actual free-flight tests. Numerical simulations have been performed using an advanced scalable unstructured flow solver on a highly- parallel Linux Cluster. Computed results have been obtained for a spinning projectile that demonstrates the ability of the virtual fly-out technique to determine the unsteady aerodynamics at transonic speeds. Our objective is to extend its capability to maneuvering projectiles. Another RBD code with flight control design capability is being coupled to CFD to eventually allow modeling of guided maneuvers. As a first step, the RBD part of this code has been demonstrated with virtual fly-out simulations on a complex finned projectile. Work is in progress to perform unguided maneuver on a canard-controlled projectile. Some basic aerodynamic results have been obtained for this case using the time-accurate sweep procedure, and are presented here. Current work is focused on performing unguided maneuver for this projectile using the virtual fly-out technique.